Performing advocacy: women's music and dance in Dagbon, northern Ghana - Stuffelbeam, Katharine (International Library of African Music, 2012)
The goal of this article is to provide a mediated experience of Dagbamba women's music and dance and to share some of the most rewarding aspects of fieldwork where music, dance, friendship, chance, and circumstance have all converged to illuminate particular moments of advocacy among women. While many Dagbamba women (and men) are Muslim, ancestral worship, herbalism, and spirit possession all coexist along with 'modern' medicine, Christianity, the internet, satellite TV, and cell phones. This article aims to highlight how women's music and dance interact within this complex cultural milieu by examining issues found in and around the music itself. This article argues that women's involvement with singing and dancing can create a transformative space where advocacy, agency, catharsis, and social critique can all take place. Several questions are of particular interest, including: What are the female roles in music and dance around Tamale? What kind of knowledge or critique is passed on or expressed through song? How does music create a transformative space for women in Tamale?
Keywords: Dance; Music; Women; African Music; Dagbon; Ghana